2017
DOI: 10.4174/astr.2017.93.5.272
|View full text |Cite
|
Sign up to set email alerts
|

Which patients with intestinal obstruction need surgery? The delta neutrophil index as an early predictive marker

Abstract: PurposePredicting the need for surgical intervention among patients with intestinal obstruction is challenging. The delta neutrophil index (DNI) has been suggested as a useful marker of immature granulocytes, which indicate an infection or sepsis. In this study, we evaluated the impact of the DNI as an early predictor of operation among patients with intestinal obstruction.MethodsA total of 171 patients who were diagnosed with postoperative intestinal obstruction were enrolled in this study. Medical records, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Of the group, 234 of the patients (53.4%) were male, while 204 were female (46.6%). The median age was 30 years (17,25). The youngest patient was aged 18 years, and the oldest 92.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the group, 234 of the patients (53.4%) were male, while 204 were female (46.6%). The median age was 30 years (17,25). The youngest patient was aged 18 years, and the oldest 92.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Recent studies have demonstrated that IG can be used as an effective inflammatory marker. [15,17,18,[25][26][27] Studies on the use of IG measurements in AA diagnosis and the discrimination between SA and CA are limited. [22,28,29] Mathews et al [28] found that an increased IG% was significant in the discrimination of acute and perforated appendicitis in the pediatric age group, but it did not bring any additional benefit to this discrimination when compared with an increased CRP level and shift to left.…”
Section: Discussionmentioning
confidence: 99%
“…60 studies were finally excluded according to the exclusion criteria: not relevant to GI diseases (n = 42), pediatric study (n = 11), abstract only study (n = 2), animal study (n = 2), study protocol (n = 1), and systematic review or meta-analysis (n = 2). The remaining 12 articles [9,[17][18][19][20][21][22][23][24][25][26][27] were included in the systematic review. Among the 12 studies, Kim JW et al [22] explored the prognostic role of DNI measured at admission day 3, and the results of the study by Cha YS et al [26] cannot be extrapolated as a form of TP, FP, FN, or TN (although we contacted corresponding author, we could not get the crude numbers of TP, FP, FN, or TN).…”
Section: Study Selectionmentioning
confidence: 99%
“…Among the 12 studies, Kim JW et al [22] explored the prognostic role of DNI measured at admission day 3, and the results of the study by Cha YS et al [26] cannot be extrapolated as a form of TP, FP, FN, or TN (although we contacted corresponding author, we could not get the crude numbers of TP, FP, FN, or TN). Therefore, these two publications were excluded in the quantitative analysis, and a total of 10 studies [9,[17][18][19][20][21][23][24][25]27] were included in the meta-analysis of diagnostic test accuracy. Figure 1 presents a flow diagram showing the process for identifying the relevant studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation